Hermetic diamond capsules for biomedical implants enabled by gold active braze alloys. (June 2015) - Lichter, Samantha G.; Escudié, Mathilde C.; Stacey, Alastair D.; Ganesan, Kumaravelu; Fox, Kate; Ahnood, Arman; Apollo, Nicholas V.; Kua, Dunstan C.; Lee, Aaron Z.; McGowan, Ceara; Saunders, Alexia L.; Burns, Owen; et al.
Abstract: As the field of biomedical implants matures the functionality of implants is rapidly increasing. In the field of neural prostheses this is particularly apparent as researchers strive to build devices that interact with highly complex neural systems such as vision, hearing, touch and movement. A retinal implant, for example, is a highly complex device and the surgery, training and rehabilitation requirements involved in deploying such devices are extensive. Ideally, such devices will be implanted only once and will continue to function effectively for the lifetime of the patient. The first and most pivotal factor that determines device longevity is the encapsulation that separates the sensitive electronics of the device from the biological environment. This paper describes the realisation of a free standing device encapsulation made from diamond, the most impervious, long lasting and biochemically inert material known. A process of laser micro-machining and brazing is described detailing the fabrication of hermetic electrical feedthroughs and laser weldable seams using a 96.4% gold active braze alloy, another material renowned for biochemical longevity. Accelerated ageing of the braze alloy, feedthroughs and hermetic capsules yielded no evidence of corrosion and no loss of hermeticity. Samples of the gold braze implanted for 15 weeks, in vivo, caused minimal histopathological reaction and results were comparable to those obtained from medical grade silicone controls. The work described represents a first account of a free standing, fully functional hermetic diamond encapsulation for biomedical implants, enabled by gold active alloy brazing and laser micro-machining.